The immune landscape of murine skeletal muscle regeneration and aging - Neuza S. Sousa; Marta Bica; Margarida F. Brás; Ana C. Sousa; Inês B. Antunes; Isabel A. Encarnação; Tiago M. Costa; Inês B. Martins; Nuno L. Barbosa-Morais; Pedro Sousa-Victor; Joana Neves (Cell Reports)
Summary: Age-related alterations in the immune system are starting to emerge as key contributors to impairments found in aged organs. A decline in regenerative capacity is a hallmark of tissue aging; however, the contribution of immune aging to regenerative failure is just starting to be explored. Here, we apply a strategy combining single-cell RNA sequencing with flow cytometry, histological analysis, and functional assays to perform a complete analysis of the immune environment of the aged regenerating skeletal muscle on a time course following injury with single-cell resolution. Our results reveal an unanticipated complexity and functional heterogeneity in immune populations within the skeletal muscle that have been regarded as homogeneous. Furthermore, we uncover a profound remodeling of both myeloid and lymphoid compartments in aging. These discoveries challenge established notions on immune regulation of skeletal muscle regeneration, providing a set of potential targets to improve skeletal muscle health and regenerative capacity in aging.